Pelatihan Implementasi Sel Fotovoltaik untuk Meningkatkan Produktivitas Santri: Studi Kasus di Pondok Pesantren At-Taubah Tirtamulya Karawang - Amir Amir; Muchammad Chusnan Aprianto; Ade Suhara; Agus Supriyanto; Dian Kristianto (Lembaga Pengembangan Kinerja Dosen, 2025)
The training on photovoltaic cell implementation at At-Taubah Islamic Boarding School, Tirtamulya, Karawang, aimed to enhance the students’ productivity through mastery of renewable energy technologies. This training was conducted as an empowerment initiative to enable students to independently apply photovoltaic cell technology to meet energy needs within the boarding school environment, while also equipping them with entrepreneurial skills in the renewable energy sector. The training methods included the delivery of basic material on photovoltaic cells, hands-on practice in assembling small-scale solar panels, and simulations of their use for lighting and simple equipment within the school. The results showed an 85% increase in students’ understanding of the working principles of photovoltaic cells, based on pre-test and post-test comparisons, along with improved skills in installing basic solar panel systems. Moreover, the training fostered student interest in developing solar panel installation and maintenance services within the surrounding community. Thus, this program contributed to enhancing the students' productivity and self-reliance while promoting clean energy utilization within the pesantren community.